Educação e religião como elementos culturais para a superação da intolerância religiosa : integração e relação na compreensão do ensino religioso - Coelho, Maria Efigênia Daltro (2009)
The purpose of this research is to understand to what extent the influence of Brazilian colonization interferes or complicates the understanding of Religious Teaching and the relationship between educator and student in the reality we live: a capital, Salvador, with a religious and cultural diversity, with an afrodescending majority. We live with a series of prejudices and religious intolerance that can turn the classes of Religious Teaching not as respectful as they should be, as well as to harm the educational practice, turning classes in a construction site of more prejudices. For this reason, we look at the need of integration between education, religion and culture for the discernment between educator and student, understanding that each one has his/her own experiences and convictions of religious and cultural life, in which tolerance and ethics are basic principles.